Energy's digital future : harnessing innovation for American resilience and national security - Jaffe, Amy Myers (Center on Global Energy Policy series., 2021)
"Disruptive digital technologies are poised to reshape world energy markets. A new wave of industrial innovation, driven by the convergence of automation, artificial intelligence, and big data analytics, is remaking energy and transportation systems in ways that could someday end the age of oil. What are the consequences-not only for the environment and for daily life but also for geopolitics and the international order? Amy Myers Jaffe provides an expert look at the promises and challenges of the future of energy, highlighting what the United States needs to do to maintain its global influence in a post-oil era. She surveys new advances coming to market in on-demand travel services, automation, logistics, energy storage, artificial intelligence, and 3-D printing and explores how this rapid pace of innovation is altering international security dynamics in fundamental ways. As the United States doubles down on fossil fuels, China is poised to become the global front-runner in a full-scale global energy transformation. In order to maintain its leadership role, Jaffe argues, the United States must embrace the digital revolution and foster American achievement. Bringing together analyses of technological innovation, energy policy, and geopolitics, Energy's Digital Future gives indispensable insight into the path the United States will need to pursue to ensure its lasting economic competitiveness and national security in a new energy age"--